Statistical overview on quality bus services in Klang Valley - Norhisham, Shuhairy; Abu Bakar, Muhammad Fadhlullah; Ahmad Tajri, Azri; Mohamad, Daud; Yatuka, Sotaro; Masjuki, Siti Aliyyah; Mohd Shkuri, Nur Syafiqah; Zaini, Nur 'Atiah (Science & Engineering Research Support Society, 2019)
Malaysia is one of the fastest grown country in Southeast Asia. Urban development in this country has a same issues should be address as developed countries around the world such as traffic congestion and increasing development area as well as population. Urban area in these countries is facing tremendous traffic congestion problem due to increasing of car ownership day by day. Therefore, there is an urge to study the current state of West Klang public buses in order to provide a thorough picture of its service ratings and performances this paper presents the statistical analysis of the stakeholder perception on the bus service for urban transportation in West Kuala Lumpur. The scope of work for this study is to investigate stakeholders’ views on bus service performance by did a survey in the west side of Klang Valley area only, which are and Puchong, Subang Jaya, Klang, Shah Alam, and Petaling Jaya. Several analyses have been conducted to identify the statistical analysis based on the data given by stakeholder.The result showed that, there are significant positive relationship between all attributes and bus performance. Result summary of hypotheses testing showed the positive relationship between variable. There are several issues should be improved to increase the quality of service for bus performance such as the on time performance buses, route service provided by operator and service coverage of bus. These are several issued have addressed by corresponding and users. Bus operator and government plays their roles tried to rectified all necessary issued and ensured that public opinion and user feedback would be heard.Feedback regarding level of service quality for bus performance should be conducted frequently